PENGUATAN JARINGAN USAHA MELALUI WADAH ORGANISASI PEREMPUAN (Studi Kasus pada Usaha Milik Warga Aisyiyah di Kota Malang) - Relawati, Rahayu (Universitas muhammadiyah palembang, 2012)
The research aimed to: 1) Identify kind of bussiness, sales and market reached by bussinesses managed by women; 2) Analyze the indicators related with omset and market coveraged; and 3) Making group of bussiness based on relation in term of backward and forward linkage. The research was conducted in Kota Malang, exactly at the area of Aisyiyah Organization. The research result were as follow. 1) Bussiness managed by women herself were generally a trading business with the prime products of food and clothes, their market coveraged were in local market of Kota Malang. The product sales were less than Rp 2,000,000.00 per month. 2) The bussiness indicator related with sales and market coveraged were bussiness orientation and professional management; capital and human resources who have professionalism; and then the ability to respon market opportunity for marketable products. 3) Groups of bussiness can be categorized based on bussiness owned by women herself or cooperation with her husband, kind of bussiness, kind of product and level of micro and small bussiness. The backward and forward linkage of their bussiness have not been found yet, however networking empowerment can be begun at the bussiness of clothes.